Proposal of a DevSecOps SCRUM-based Methodology for Software Development with Quality - Xochitototl Cote, Itzel (2024)
Collaboration in software development teams often requires effective activity management. Agile methodologies enable managing changes; however, fostering a culture of cross-functional collaboration within the organization and shared responsibility for security in development facilitates comprehensive communication. This provides stakeholders with better decision-making tools. The aim of this paper is to outline a methodology proposal for managing software development projects based on DevSecOps and Scrum. Subsequently, the methodology is tested in two case studies, and the results are presented, highlighting improvements in delivery times and software development quality.  Finally, it discusses how integrating agile methodologies like DevSecOps and Scrum in software development project management provides a robust framework to adapt to changes and enhance the quality of the final product.